The influence of positive psychology on PAI (Islamic Education) learning on social behavior and empathy among students - Fitriana Setiawati; Wasith Achadi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research aims to examine the influence of positive psychology in Islamic Religious Education (PAI) learning on the development of students' social behavior and empathy. This type of qualitative research uses the method of literature review by analyzing various literature, scientific journals, books and related documents. Positive psychology offers an innovative approach that is in line with PAI values, such as gratitude (Grattiude), compassion, mindfulness, and empathy, which can support student character formation. The research results show that the integration of positive psychology in PAI learning can improve students' ability to understand other people's feelings and show better prosocial behavior. This research recommendation includes the development of a PAI curriculum based on positive psychology to create more effective and meaningful learning.